Small States and the Struggle for Power in the Arctic Region: A Case Study of Denmark - Lukšaitė, Gabija (Politologija, 2019)
This paper examines the specifics of foreign policy strategies used by Denmark as a small state in the Arctic region. Based upon a number of theoretical approaches in terms of analyzing small state foreign policy, this study is primarily focused on how small states manage to pursue their goals in an international environment typically dominated by large powers.